Doping GaP Core–Shell Nanowire pn‐Junctions: A Study by Off‐Axis Electron Holography. Issue 22 (5th February 2015) - Yazdi, Sadegh; Berg, Alexander; Borgström, Magnus T.; Kasama, Takeshi; Beleggia, Marco; Samuelson, Lars; Wagner, Jakob B.
<x xml:space="preserve">Abstract</x> The doping process in GaP core–shell nanowire pn‐junctions using different precursors is evaluated by mapping the nanowires' electrostatic potential distribution by means of off‐axis electron holography. Three precursors, triethyltin (TESn), ditertiarybutylselenide, and silane are investigated for n‐type doping of nanowire shells; among them, TESn is shown to be the most efficient precursor. Off‐axis electron holography reveals higher electrostatic potentials in the regions of nanowire cores grown by the vapor–liquid–solid (VLS) mechanism (axial growth) than the regions grown parasitically by the vapor–solid (VS) mechanism (radial growth), attributed to different incorporation efficiency between VLS and VS of unintentional p‐type carbon doping originating from the trimethylgallium precursor. This study shows that off‐axis electron holography of doped nanowires is unique in terms of the ability to map the electrostatic potential and thereby the active dopant distribution with high spatial resolution.